Evaluation of changes in sleep breathing patterns after primary palatoplasty in cleft children - Justice E. Reilly; Craig J. H.; Neil A. Gibson; Tony Moores; Arup K. Ray; Mark F. Devlin; David M. Wynne (Dentitio, 2014)
Introduction: There is a need to more clearly understand the characteristics of breathing patterns in children with cleft palate inthe first year of life, as there is little data available to guide current practice. Pierre Robin patients are known to have a higher incidence, however we hypothesised sleep breathing disturbance is not confined to this sub-group of cleft patient. Methods: We conducted a prospective observational study of sleep disordered breathing patterns in a cohort of infants with oronasal clefts (cleft palate with or without cleft lip) to describe the spectrum of sleep breathing patterns both pre and post palate repair. Sleep breathing studies were performed pre- and post-operatively in sequential infants referred to a regional cleft lip andpalate unit. Results of sleep breathing studies were analysed according to American Academy of Sleep Medicine scoring guidelines and correlated with clinical history and details of peri-operative respiratory compromise. The degree of sleep disordered breathingwas characterised using desaturation indices (number of desaturations from baseline SpO2 of >=4%, per hour). Results: Thirty-nine infants were included in this study, twenty-five female and fourteen male. Twelve had isolated Cleft Palate aspart of an associated syndrome. Patients were categorised into Isolated Cleft Palate, Isolated Cleft Palate in the context of Pierre Robin Sequence, and those with Cleft Lip and Palate. All groups demonstrated some degree of sleep breathing abnormality. Not unsurprisingly the eight infants with Pierre Robin Sequence had a significantly higher desaturation index before surgicalintervention (p=0.043), and were more likely to require a pre-operative airway intervention (p=0.009). Palate repair in this group did not alter the relative distribution of patients in each severity category of sleep disorder breathing. Surgical repair ofthe secondary palate in the remaining children was associated with some improvement but by no means complete resolution of their sleep disordered breathing patterns. Conclusions: We conclude that sleep breathing disturbance is not confined to Pierre Robin patients alone and all cleft palate patients should undergo pre-operative and post-operative sleep breathing analysis.